Oxidant-Sensing Pathways in the Responses of Fungal Pathogens to Chemical Stress Signals - Simaan, Hiba; Lev, Sophie; Horwitz, Benjamin A. (Frontiers in Microbiology, 2019)
Host defenses expose fungal pathogens to oxidants and antimicrobial chemicals. The fungal cell employs conserved eukaryotic signaling pathways and dedicated transcription factors to program its response to these stresses. The oxidant-sensitive transcription factor of yeast, YAP1, and its orthologs in filamentous fungi, are central to tolerance to oxidative stress. The C-terminal domain of YAP1 contains cysteine residues that, under oxidizing conditions, form an intramolecular disulfide bridge locking the molecule in a conformation where the nuclear export sequence is masked. YAP1 accumulates in the nucleus, promoting transcription of genes that provide the cell with the ability to counteract oxidative stress. Chemicals including xenobiotics and plant signals can also promote YAP1 nuclearization in yeast and filamentous fungi. This could happen via direct or indirect oxidative stress, or by a different biochemical pathway. Plant phenolics are known antioxidants, yet they have been shown to elicit cellular responses that would usually be triggered to counter oxidant stress. Here we will discuss the evidence that YAP1 and MAPK pathways respond to phenolic compounds. Following this and other examples, we explore here how oxidative-stress sensing networks of fungi might have evolved to detect chemical stressors. Furthermore, we draw functional parallels between fungal YAP1 and mammalian Keap1/Nrf2 signaling systems.